Work Stress and Its Association with Cardiovascular Events in Occupational Populations: A Systematic Review and Meta-analysis - Hui Dong; Lan Sheng Yang; Zhong Yu Yan; Yu Xin Gou; Ying Zhang; Wei Luan; Wu Jing (Asian Journal of Social Health and Behavior)
Introduction: Cardiovascular disease (CVD) is the top global killer, with work stress as a risk factor. The choice of assessment tools for work stress significantly affects our understanding of its role in CVD outcomes. This systematic review and meta-analysis focused on comparing the efficacy of different work stress assessment tools in predicting cardiovascular events. Methods: We searched PubMed, Web of Science, Scopus, Cochrane, and Embase databases through December 2023 for cohort studies quantifying the association between work stress and cardiovascular events. Using predefined criteria, we extracted data and conducted random- or fixed-effects meta-analyses to calculate pooled hazard ratios (HRs) with 95% confidence intervals (CIs). Sensitivity analyses were conducted using the literature-by-exclusion method and the fill-and-trim method. Results: Eighteen articles involving 257,101 subjects were included. Work stress increased the risk of cardiovascular events by 26% (HR = 1.26; 95%CI: 1.19–1.34; P < 0.001). The job content questionnaire showed a significant association (HR = 1.25; 95% CI: 1.17–1.34; P < 0.001; I2 = 11.4%) The effort–reward imbalance scale also indicated significance but with heterogeneity (HR = 1.30; 95%CI: 1.15–1.47; P = 0.084; I2 = 54.9%). When categorized by event type, increased work stress is linked to an elevated risk of cardiovascular events, particularly coronary heart disease and myocardial infarction, though not with stroke. Conclusion: The JCQ is recommended for studying work stress and cardiovascular health. While publication bias is possible, our findings are robust. However, limitations due to heterogeneity and studies’ number highlight the need for further research.